PELATIHAN PENGELOLAAN KEUANGAN DALAM MENDUKUNG PENGEMBANGAN USAHA DI DESA KASTURI KABUPATEN KUNINGAN - Nurfatimah, Siti Nuke; Wiharno, Herma; Syarifudin, Syahrul (FKIP Universitas Wisnuwardhana, 2024)
Abstract: MSME actors in Kasturi Village, Kuningan Regency still have limited knowledge and practice in managing business finances, both from a lack of literacy and minimal business recording and bookkeeping. In fact, some of them still combine business finances and personal finances. This will of course have a negative impact on the sustainability of these MSMEs. Therefore, this service to the community aims to increase the literacy and ability of MSME players in making good business financial records and bookkeeping as well as carrying out financial management separate from personal wallets so as to improve control of business financial flows to be able to develop their business. The approach used to overcome this problem is through providing literacy, financial recording training and business bookkeeping training which is carried out over 3 days. The results obtained from this activity were that all participants were able to understand the importance of managing business finances and were able to make good daily records and business bookkeeping so that they were able to improve their skills in managing business finances and controlling business finances. Apart from that, it is hoped that the financial management process that has been provided can be implemented to support the sustainability and development of these MSMEs. Keywords : MSMEs Financial Management, MSMEs Financial Recording and Bookkeeping